LEGAL ANALYSIS OF THE DOCTRINE OF ESSENTIAL FACILITIES DUTIES IN THE INDONESIA COMPETITION LAW - Nandi Wardhana (Fakultas Hukum, Universitas Diponegoro, 2018)
Indonesian competition law today requires a renewal of one of them concerning the doctrine of essential facilities duties. The doctrine essential facilities duties is a doctrine imposed on a dominant business actor who has access to essential facilities to provide access for competing business actors to use the facility. Regulation of essential facilities duties are needed to reduce dominance of a dominant firm in a particular market. This study uses a statutory approach, conceptual approach, and a comparative approach between the arrangements in the United States, Europe and Indonesia. The approach is expected to illustrate, harmonize problems arising, and provide better legal protection in the world of business competition. The doctrine essential facilities duties were first applied in the United States and then followed by European countries. The doctrine of essential facilities duties in the United States is based on the sherman act and uses theapproach rule of reason. The doctrine of essential facilities duties in European countries based on EC focuses on refusal to deal. The doctrine of essential facilities duties is explicitly implied in Law No. 5 of 1999. From this study it is concluded that the regulation on essential facilities duties in Law No. 5 of 1999 still can not provide a good legal protection for business competition in Indonesia.